Prognostic value of quantitative fluorodeoxyglucose measurements in newly diagnosed metastatic breast cancer. (12th September 2013) - Ulaner, Gary A.; Eaton, Anne; Morris, Patrick G.; Lilienstein, Joshua; Jhaveri, Komal; Patil, Sujata; Fazio, Maurizio; Larson, Steven; Hudis, Clifford A.; Jochelson, Maxine S.
Abstract The aim of this study was to determine the prognostic value of quantitative fluorodeoxyglucose (FDG) measurements (maximum standardized uptake value [SUVmax], metabolic tumor volume [MTV], and total lesion glycolysis [TLG]) in patients with newly diagnosed metastatic breast cancer (MBC). An IRB‐approved retrospective review was performed of patients who underwent FDG positron emission tomography (PET)/computed tomography (CT) from 1/02 to 12/08 within 60 days of diagnosis MBC. Patients with FDG‐avid lesions without receiving chemotherapy in the prior 30 days were included. Target lesions in bone, lymph node (LN), liver, and lung were analyzed for SUVmax, MTV, and TLG. Medical records were reviewed for patient characteristics and overall survival (OS). Cox regression was used to test associations between quantitative FDG measurements and OS. A total of 253 patients were identified with disease in bone (n = 150), LN (n = 162), liver (n = 48), and lung (n = 66) at the time of metastatic diagnosis. Higher SUVmax tertile was associated with worse OS in bone metastases (highest vs. lowest tertile hazard ratio [HR] = 3.1, P < 0.01), but not in LN, liver or lung (all P > 0.1). Higher MTV tertile was associated with worse OS in LN (HR = 2.4, P < 0.01) and liver (HR = 3.0, P = 0.02) metastases, but not in bone (P = 0.22) or lung (P = 0.14). Higher TLG tertile was associated with worse OS in bone (HR = 2.2, P = 0.02), LN (HR = 2.3, P < 0.01), and liver (HR = 4.9, P < 0.01) metastases, but not in lung (P = 0.19). We conclude measures of FDG avidity are prognostic biomarkers in newly diagnosed MBC. SUVmax and TLG were both predictors of survival in breast cancer patients with bone metastases. TLG may be a more informative biomarker of OS than SUVmax for patients with LN and liver metastases.